2018
DOI: 10.1111/birt.12402
|View full text |Cite
|
Sign up to set email alerts
|

Severe perineal trauma among women undergoing vaginal birth after cesarean delivery: A population‐based cohort study

Abstract: Background To examine risk of severe perineal trauma among nulliparous women and those undergoing vaginal birth after cesarean delivery (VBAC). Methods This is a population‐based cohort study of all births to women with their two first consecutive singleton pregnancies in Stockholm‐Gotland Sweden between 2008 and 2014. Risk of severe perineal trauma was compared between nulliparous women and those undergoing VBAC with severe perineal trauma being the main outcome measure. Associations between indication and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…In women with a previous CS, there was a lower OASIS rate after induced labor than after spontaneous onset. In contrast to previous studies, this observation is based on attempted vaginal births after previous CS, not achieved vaginal births 27–30 . The PPH rate was higher in term cephalic singleton births by prelabor CS than in spontaneous or induced labor for both nulliparous and multiparous women with unscarred uterus.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In women with a previous CS, there was a lower OASIS rate after induced labor than after spontaneous onset. In contrast to previous studies, this observation is based on attempted vaginal births after previous CS, not achieved vaginal births 27–30 . The PPH rate was higher in term cephalic singleton births by prelabor CS than in spontaneous or induced labor for both nulliparous and multiparous women with unscarred uterus.…”
Section: Discussionmentioning
confidence: 78%
“…In contrast to previous studies, this observation is based on attempted vaginal births after previous CS, not achieved vaginal births. [27][28][29][30] The PPH rate was higher in term cephalic singleton births by prelabor CS than in spontaneous or induced labor for both nulliparous and multiparous women with unscarred uterus. Furthermore, spontaneous onset of labor was associated with lower proportions of Apgar score <7 at 5 minutes compared with prelabor CS, which challenges the belief that prelabor CS is a shortcut to better neonatal health.…”
Section: Discussionmentioning
confidence: 95%
“…Other complications of severe perineal trauma are pain [ 3 ], dyspareunia [ 4 ], an altered body image, and psychosocial problems [ 5 7 ]. Risk factors for severe perineal trauma are giving birth vaginally for the first time, having an assisted vaginal birth, giving birth vaginally after a previous caesarean section, or giving birth to a baby that weighs more than 4000 g, ethnicity, and the risk increases with age [ 8 11 ]. Some of the methods used to prevent perineal injuries have been evaluated in clinical trials, but there are still gaps in the evidence [ 12 ].…”
Section: Background {6a}mentioning
confidence: 99%
“…However, compared with vaginal birth in primiparous women, there is emerging evidence suggesting successful VBAC is also associated with an increased risk of obstetric anal sphincter injury (9,10,15). Past studies in this field have been limited by small cohort sizes, lack of broader generalisability (limited to a single hospital cohort) or outdated methodology (such as a reliance on complete case records only, which may lead to ascertainment bias) (16).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have consistently suggested that women having a VBAC are up to 1.4-fold more likely to sustain significant perineal injury compared with their primiparous counterparts (8,9,15). And yet, the risk of perineal injury is still only peripherally acknowledged in many professional guidelines (17,18) and is not routinely included in antenatal counselling of women considering a VBAC.…”
Section: Introductionmentioning
confidence: 99%